The impact of alexithymia, anxiety, social pressure, and academic burnout on depression in Chinese university students: an analysis based on SEM - Mingyang Sun; Ming Piao; Zhaona Jia (BMC Psychology)
Abstract Background With societal development and increasing talent demands, college students face escalating pressures primarily stemming from academic burdens, uncertainties about the future, and complex social environments. These pressures have profound effects on mental health, particularly negatively impacting emotions and behavior. In this context, depressive symptoms are becoming increasingly prevalent among college students. Given the potential links between emotional disorders, anxiety, social pressure, and academic burnout, this study aims to explore how these factors collectively influence depression in college students. Methods This study utilized a questionnaire approach, resulting in 599 valid responses. The collected data were analyzed using Smart-PLS for SEM to investigate the relationships among the variables. Results The SEM analysis indicated that the comprehensive model explained 83.2% of the variance in depression. Alexithymia significantly positively predicted anxiety and social pressure. Academic burnout significantly positively influenced social pressure, anxiety, and depression. Anxiety played a partial mediating role in the impact of alexithymia and academic burnout on depression. Social pressure and alexithymia did not have a significant positive impact on depression. In addition, there is a significant gender difference in the impact of academic burnout on depression, with the path coefficient for males being significantly higher than that for females. Conclusion This study validated the complex relationships among alexithymia, anxiety, social pressure, academic burnout, and depression. As an emotional expression disorder, alexithymia not only directly impacts anxiety levels in college students but also indirectly affects depression through anxiety. Furthermore, the positive influence of academic burnout on anxiety and depression indicates that excessive academic burdens are significant sources of mental health issues for college students. This research offers new insights into understanding college students’ mental health issues, aiming to provide more comprehensive intervention strategies for their psychological well-being.